2019
DOI: 10.1080/10826084.2018.1521429
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Stand: An Untapped Strategy to Reduce Waterpipe Smoking in Adolescents

Abstract: Introduction: Waterpipe use amongst adolescents is on the rise globally. Thus, there is a need to understand adolescents 'attitudes towards and perceptions of waterpipe use in order to develop specific interventions against this form of tobacco use. Methods: Focus group interviews were conducted among 37 Swedish adolescents (14 boys and 23 girls) from grades 10 to 12. Waterpipe users and nonusers were interviewed separately, with two groups each for users and nonusers. Interviews were audiotaped, transcribed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Studies reported a high prevalence of WPS use among adolescents globally 9,10 . In the Mediterranean, the use of WPS is an important public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported a high prevalence of WPS use among adolescents globally 9,10 . In the Mediterranean, the use of WPS is an important public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study on 37 Swedish adolescents, reasons for using hookah were meeting friends, being accepted by a group, or using hookah as a criterion for admission into a group. Moreover, participants did not have a negative concerning hookah smoking (47), and related studies have indicated that there was a strong link between hookah use and having friends who are addicted to hookah or smoking cigarettes (48).…”
Section: Social Domainmentioning
confidence: 85%
“…Dabei sollte auch dem verbreiteten Irrglauben begegnet werden, dass Shisharauchen weniger gefährlich sei als das Rauchen von Zigaretten [26]. Solche Risikoinformationen sollten bestenfalls schon in der Schule vermittelt werden, da viele bereits im Jugendalter aufgrund von sozialem Druck und Neugier anfangen, Shishas zu rauchen [27]. Besitzerinnenund Besitzervon Holzpelletheizungen könnten hingegen eher über regionale oder lokale Informationsangebote in ländlichen Räumen erreicht werden, zum Beispiel mit Veranstaltungen, Infoständen, Plakaten oder Artikeln in Lokalzeitungen.…”
Section: Risikowahrnehmung Und Wissen üBer Kohlenmonoxid Bei Risikogrunclassified